2017
DOI: 10.1007/s10620-017-4525-y
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Burden of Diverticulitis in the USA, 2006–2013

Abstract: Goals The aim of this study was to analyze recent trends in ED visits for diverticulitis between 2006 and 2013. Background Acute diverticulitis is a serious medical condition that frequently leads to emergency department (ED) visits, hospitalizations, and surgeries resulting in a significant health care burden. Methods Data were obtained from the National Emergency Department Sample (NEDS) records in which diverticulitis (ICD-9-CM codes 562.11 and 562.13) was the primary diagnosis in the ED between 2006 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 33 publications
0
44
0
3
Order By: Relevance
“…Delvaux [61] reported that there were almost 800,000 hospital admissions for diverticular disease in European countries. As a countermeasure for the burden of diverticular disease, a systematic review reported that there was no difference in failure rates of medical treatment (6.5 vs. 4.6%) and recurrence rates (13.0 vs. 12.1%) between patients who received ambulatory care and those who received inpatient care for uncomplicated diverticulitis [62]. Ambulatory treatment was associated with daily cost savings of between 600 and 1,900 EUR per patient treated.…”
Section: Burden Of Diverticular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Delvaux [61] reported that there were almost 800,000 hospital admissions for diverticular disease in European countries. As a countermeasure for the burden of diverticular disease, a systematic review reported that there was no difference in failure rates of medical treatment (6.5 vs. 4.6%) and recurrence rates (13.0 vs. 12.1%) between patients who received ambulatory care and those who received inpatient care for uncomplicated diverticulitis [62]. Ambulatory treatment was associated with daily cost savings of between 600 and 1,900 EUR per patient treated.…”
Section: Burden Of Diverticular Diseasementioning
confidence: 99%
“…In patients for whom surgery is indicated, a recent meta-analysis showed that, compared to open surgery, laparoscopic surgery for diverticular disease was associated with a significantly reduced length of stay and fewer complications [66]. Recently, Bollom et al [62] reported that the number of emergency department visits due to diverticulitis and associated costs continued to rise between 2006 and 2013, whereas the rate of bowel surgeries and inpatient admissions through the emergency department for diverticulitis has decreased [67]. Diverticular bleeding can be massive and recurs frequently; therefore, it involves repeated examination, hospitalization, and blood transfusion.…”
Section: Burden Of Diverticular Diseasementioning
confidence: 99%
“…During the twentieth century, the incidence of acute diverticulitis has been rising and so have the treatment costs [1][2][3]. Acute diverticulitis is classified as uncomplicated or complicated.…”
Section: Introductionmentioning
confidence: 99%
“…1 Between 2000 and 2009, admissions for diverticulitis increased 41%, representing over 219 000 discharges and US$2.1 billion dollars in inpatient charges. 2 As the population ages, these numbers are likely to increase, since at least 60% of people over the age of 60 have diverticulosis and 10%–25% will progress to diverticulitis at some point. 2-3 Though 85% of these episodes are likely to be uncomplicated, 15%–30% will experience at least one recurrence.…”
mentioning
confidence: 99%
“…2 As the population ages, these numbers are likely to increase, since at least 60% of people over the age of 60 have diverticulosis and 10%–25% will progress to diverticulitis at some point. 2-3 Though 85% of these episodes are likely to be uncomplicated, 15%–30% will experience at least one recurrence. 3…”
mentioning
confidence: 99%